Pengelolaan Kelas Dalam Pembelajaran Tematik di SD/MI - Syahidan Nurdin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Classroom management is an effort made by teachers to create and maintain classroom conditions so that they remain normal and optimal in carrying out learning so that it can continue to run effectively and efficiently. Thematic learning is integrated learning that uses themes to link several subjects so that it can provide meaningful experiences to students. The aim of this research is to describe classroom management in thematic learning. This research method is a descriptive approach with a qualitative research type. The results of this research indicate that the classroom management carried out by teachers at SDN 2 Trienggadeng Pidie Jaya has generally been carried out well and teachers have utilized the available classroom facilities and infrastructure.